Interaction effects and mechanism of Pb pollution and soil microorganism in the presence of earthworm. (April 2017) - Liu, Gao; Ling, Siyuan; Zhan, Xiuping; Lin, Zhifen; Zhang, Wei; Lin, Kuangfei
Abstract: Heavy metals usually cause great damage to soil ecosystem. Lead (Pb) was chosen as a research object in the present study. Here repeated exposure of Pb was designed for the soil artificially contaminated. A laboratory study was conducted to determine the changes in the Pb availability and biological activity in the presence of earthworm, and the risk assessment code (RAC) was applied to evaluate the remediated soil. Results demonstrated that Pb gradually transformed to more stable fractions (OMB- and FeMnOX-Pb) under microbial action, indicating the risk level of Pb was declined. On the other hand, Pb also caused the inhibition of soil respiration and microbial biomass, and the higher the concentration of Pb, the stronger the inhibition; While in the presence of earthworm, it could absorb Pb and facilitate microbial activity, reflected the decrease of Pb content and the increase of respiration intensity in soil, as well as microbial biomass. Additionally, a good dose-response relationship between EXCH-Pb content and respiration intensity might provide a basis for ecological risk assessment. Highlights: Repeated exposure of Pb was applied to the soil artificially contaminated. Biological toxicity and bioremediation property of pollutants were simultaneously explored. Exp correlation between EXCH-Pb level and soil respiration was clearly observed.